Interaction of Small Hydrocarbons with Fusion Relevant Beryllium Thin Films - Bilal Rasul; Aroog g (Mehran University Research Journal of Engineering and Technology, 2021)
Ion-surface collision studies are carried out with small deuterated hydrocarbon cations i.e. CDx + with x = 2-4 colliding with fusion relevant Beryllium (Be) thin films with ions incident energy as low as 0 eV and as high as Ein = 100 eV. Be films are coated on stainless steel surface by the technique of Thermionic Vacuum Arc (TVA); a novel thin film deposition method with primary as well distinguished characteristic of control of ion flux and respective dose towards the substrate. Prior to scattering, methane-d4 99 atom % D is ionized by electron impact and ions are mass and energy analyzed. Ionization and collisions are performed in ultra high vacuum conditions. In these kinds of collision experiments, we have recorded secondary ion mass spectra and plotted respective incident energy resolved abundances of secondary product ions. Relative abundances in percentage of total secondary ions are plotted and it is observed that such beryllium films can accumulate charged hydrocarbon layers as surface adsorbates. These self assembled layers play a primary role in surface-scattering of primary ions. Moreover, it is seen that bond dissociation energy in lighter hydrocarbons is higher than that for heavier species and shows primarily that the deuterium atoms are loosely bounded to carbon atoms in heavier hydrocarbons than in lighter ones.